Psychoanalysis and culture. Ricoeur’s reading of Freud - Węgrzyn, Marta (Hybris, 2016)
The subject of “Psychoanalysis and culture” is one of the three main topic lines Ricoeur moves in his essays on Freud. Ricoeur takes the intellectual challenge of comprehensive interpretation of the Freud’s work and shows his subtle understanding of Freud’s philosophical views. Ricouer tries his best to translate the language of psychoanalysis into philosophy. At the same time he’s aware that psychoanalysis is a profound challenge for someone who previously dealt with phenomenology, existential philosophy and language sciences. Ricoeur sets himself reflective context within his moves. He sets a basis on Freudian interpretations and analysis of art, cultural and psychic phenomena. Ricouer proposes to take research on psychoanalysis in relation to the hermeneutic tradition, and more specifically, the hermeneutic conception of meaning. However Freud in his work often deals with the meaning of dreams, slips or neurotic symptoms. Such understanding of psychoanalysis allows for a deeper interpretation of human internal states, it also interprets the signs wielding a mental life. So how does look and what is the project of hermeneutic interpretation of psychoanalysis? What is the place of psychoanalysis in the culture movement?